Extensive Listening: Indonesian Teacher Educators’ and Student Teachers’ Perspectives and Experiences in Initial Teacher Education Context - Irmayani Irmayani; Refi Ranto Rozak; Ahmad Zubaidi Amrullah; Maslakhatin Maslakhatin (Edulitics (Education, Literature, and Linguistics) Journal, 2023)
This case study examines teacher educators and student teachers’ experiences and perspectives in East Java, Indonesia, with the aim of investigating Extensive Listening (EL) integration to the Initial Teacher Education (ITE) as a prescribed language curriculum program. Data were collected from semi-structured interviews with the three teacher educators and six student teachers. The results revealed variations in how EL programs are practiced among various institutions, underscoring the necessity for a standardized curriculum to incorporate EL into language teaching programs. Teacher educators performed resourcefulness by creatively using online resources to compensate for the absence of formal EL training. The independent listening practices of student teachers emphasizing the importance of authentic materials that align with their personal interests, using technology to promote self-directed learning. This research serves as an initial exploration of the potential of EL in the ITE context in Indonesia. Both teacher educators and student teachers hold crucial roles in driving curriculum innovation by advocating for the acknowledgment and inclusion of EL within the language curriculum.